Hochschild homology and cohomology of generalized weyl algebras: The quantum case - Solotar, Andrea Leonor (2011)
We determine the Hochschild homology and cohomology of the generalized Weyl algebras of rank one which are of 'quantum' type in all but a few exceptional cases.